Open esophagectomy as a treatment of choice for esophageal cancerand a successful outcome at the University Clinic in Skopje, North Macedonia: a case report - Kondov B; Antovic, S; Kondov G; Jakupi N; Karagjozov P; Colanceski, R; Jovev, S; Cvetanovski V; Andonovska B; Duka R (University Ss. Cyril and Methodius, Medical Faculty in Skopje, 2022)
Esophageal cancer is one of the least studied cancers and has high mortality rates, mainly because it is diagnosed at rather late stage. It requires urgent attention and in patients where surgery is feasible, it is immediately performed. There is a considerable variation in terms of the surgical approach in different countries, but open esophagectomy is a treatment of choice. This study describes a case of esophageal squamous cell carcinoma that was successfully treated with open esophagectomy and therefore provides information about the present state of esophageal cancer surgery at the University Clinic in Skopje, North Macedonia. The patient underwent clinical examination after which she was admitted to our department for surgical treatment. Esophagography and CT imaging were done pre- and postoperatively and no complications were noted after surgery. The patient was discharged and a written informed consent was obtained for publication of this case and any accompanying images.
Keywords: esophageal cancer; squamous cell carcinoma; surgical treatment; open esophagectomy